(untitled) - Faiz, Asif (Washington D.C, 1996)
This book consists of the following many parts such as emission standards and regulations, quantifying vehicle emissions, vehicle technology for controlling emissions, controlling emissions from in-use-vihicles, and fuel options for controlling emissions.
Keywords: Motor,Motor vehicles; Exhaust gas,Law and legislation,Pollution control devices